The Prognostic and Clinical Value of Neutrophil-to-Lymphocyte Ratio (NLR) in Ovarian Cancer: A Systematic Review and Meta-analysis: NLR's Role in Ovarian Cancer: Review & Analysis - Zhang, Zihan; Lang, Jinghe (Journal of Medical Biochemistry, 2023)
Background: Ovarian cancer (OC) is a major gynecological malignancy with varying prognosis. The Neutrophil-to-Lymphocyte Ratio (NLR) has been proposed as a potential prognostic biomarker. This study aimed to evaluate the prognostic and clinical value of NLR in OC.Methods: A systematic review and meta-analysis were performed following PRISMA guidelines, including studies that evaluated the association between NLR and survival outcomes in OC patients. Search was performed in PubMed, Embase, Web of Science, and Cochrane Library databases. Quality assessment was done using Newcastle-Ottawa Scale (NOS). Heterogeneity was assessed, and pooled hazard ratios (HRs) were calculated using fixed or random-effects models as appropriate.Results: Twenty studies involving various ethnicities, ages, and sample sizes were included. A high NLR was found to be inversely correlated with overall survival (OS) (HR= 1.21, 95% CI 1.09-1.34, P